Express - a method of forming a representative expert coalition based on an extended correlation matrix - R. A. Zhilin (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The aim of the study is to develop an effective express method for the formation of a representative expert coalition based on the analysis of correlations between expert opinions.Method. It is proposed to use an extended correlation matrix, which takes into account not only the strength of the correlation between the experts’ ratings, but also the average value of the ratings for the entire set of highly qualified specialists. This matrix will take into account the diversity of opinions and preferences of highly qualified specialists, as well as provide a high degree of representativeness in making collective decisions.Result. Verification of the obtained results was carried out on the example of polls of police officers in relation to violators of security systems. A significant number of various calculations determines the implementation of the developed numerical method using a computer. This express method is a useful tool for the rapid and efficient formation of representative expert coalitions and decision-making based on the opinions of a large number of highly qualified specialists.Conclusion. The proposed method can be applied in various scientific and technical fields, such as expert systems, multi-criteria decision making, risk assessment, and other situations where it is necessary to combine the opinions of a large number of experts.